Determination of heavy metals concentration in food waste compost on root uptake of capsicum annuum L - Abu Samah, Mohd Armi; Hassan, Nur Shahirah; Mohd. Hussain, Mohd. Ramzi; Ibrahim, Mohd Zulfadzli; Mohd Jan, Nurul Hafiza; Kamarudin, Mohd Khairul Amri (Science and Engineering Research Support Society, 2020)
The increasing amount of food waste in Malaysia in recent years has brought many serious environmental issues to the country where it affects the nation’s solid waste management framework. As for now, the Food Waste Management Development Plan for Industry, Commercial and Institution Sector (2016-2026) is taking actions in order to achieve efficient and effective food waste management. One of the strategies listed is by enhancing food waste treatment at source through composting due to its environmental and economic benefits. However, an excessive amount of heavy metals and minerals will pose a harmful effect to the plant and soil by disrupting the microbial biota that is responsible for plant growth. This study was conducted to provide information on heavy metals concentration contained in Food Waste Compost (FWC) and root of Capsicum annuum L. (chilli plant). The study was consist of several stages, starting from the preparation of food waste compost, planting process, treatment application, harvesting, and collecting data followed by laboratory analysis and finalised with analysing data statistically. A total number of 16 experimental units involving four levels of soil treatment (T1 = no FWC, T2 = 31.9 FWC / week, T3 = 81.9 FWC / week, T4 = 11.9 FWC / week) with a set of replications were conducted in the glasshouse. The experimental design was in the form of randomised complete block design (RCBD). The heavy metals in food waste compost, such as lead (Pb), nickel (Ni), chromium (Cr), copper (Cu), zinc (Zn) and cadmium (Cd) were determined using Inductively Coupled Plasma Mass Spectroscopy (ICP- MS). The average concentrations for the heavy metals were Pb (1.0 ± 0.455 ppm), Ni (140.0 ± 9.899 ppm), Cr (446.2 ± 36.770 ppm), Cu (10.9 ± 1.438 ppm) and Zn (19.0 ± 5.940 ppm). However, concentration for Cd was failed to be determined due to its below detectable level readings. From these six metals, Ni and Cr were found higher in a concentration exceeding the heavy metal limits in compost-based on standards from European countries and Canada. The concentration of Cr and Ni were later determined in the root of Capsicum annuum L. with different compost treatment rates using Atomic Absorption Spectroscopy (AAS). Average concentration in root for Ni were (T1: 1.68 ± 0.020 ppm), (T2: 2.25 ± 0.274 ppm), (T3: 2.10 ± 0.390 ppm) and (T4: 2.19 ± 0.274 ppm), meanwhile for Cr were (T1: 1.40 ± 0.04 ppm), (T2: 1.88 ± 0.679 ppm), (T3: 1.90 ± 0.545 ppm) and (T4: 1.88 ± 0.474 ppm). Both metals in all treatments exceeded the permissible limit listed by the World Health Organization (WHO), which for Ni is 1.5 ppm and for Cr is 1.3 ppm with the obtained data being provisionally insignificant (p> 0.05). Based on the findings of this study, it can be inferred that the food waste compost contained Ni and Cr exceeding the permissible limit in soil treatment and root of Capsicum annuum L.